Tratamiento interdisciplinario ortodóntico y periodontal en un paciente con periodontitis, tratada y controlada. (2021)
Periodontitis is a pathology that produces a destructive host response on the supporting tissues of the tooth. Periodontal complications and loss of posterior teeth can lead to collapse of the posterior occlusion and reduction in vertical dimension, causing proclination, spacing, and excessive eruption of anterior teeth.